Design and Implementation of IoT-Based Burglary Detection System - Mokhalad Mahdi Jassem; Mohammed Al-Nouman (Universitas Ahmad Dahlan, 2023)
This paper aims to design and implement an IoT-based anti-theft security system. The system uses fingerprint recognition technology to grant access to a building only if the fingerprint matches the stored data. In case of unauthorized access attempts, the system captures a photo of the person and sends an immediate alert to the homeowner via the Telegram API. The proposed paper methodology involves analyzing existing systems, identifying research gaps, and developing a generally implementable framework. The proposed system is implemented using Raspberry Pi as the main control unit and incorporates components like the R305 Fingerprint Recognition Sensor, Camera Pi for video surveillance, and additional hardware for door control and sensor integration. Through practical testing, the implemented system demonstrates reliable burglary detection and notification capabilities, enhancing home or building security. Finally, the obtained research results offer valuable insights for future developments in anti-theft security systems.